Pengaruh Capital Adequacy Ratio dan Loan to Deposit Ratio terhadap Net Interest Margin di Bank Jabar Banten - Fauzi, Yasir; Fuadi, Faisal Ridwan; Nurkamali, Ahmad (JURNAL KAJIAN ISLAM MODERN, 2024)
This research was motivated by fluctuations in CAR and LDR every year at Bank Jabar Banten for the 2018-2022 period, causing NIM to fluctuate. This research aims to find out how CAR and LDR influence NIM, both partially and simultaneously. The research objects in this report are CAR, LDR and NIM contained in financial reports. The type of research is quantitative with an associative approach. The type of data used is secondary data and uses data collection techniques through documentation and literature study. Meanwhile, the sampling technique is non-probability sampling, with a population of all quarterly financial reports. The research results show that there is an influence of CAR on NIM with the results of the t test where the value of tcount > ttable (2.720 > 1.73406), there is no significant influence of LDR on NIM with the results of the t test where the value of tcount < ttable (0.653 < 1.73406). Meanwhile, CAR and LDR simultaneously influence NIM. This is indicated by the value Fcount > Ftable (10.58 > 3.59), with an R Square of 0.3025 (30.25%), which means the NIM variable can be explained by the CAR and LDR variables of 30.25%.